Psychosocial characteristics of victims of special fraud among Japanese older adults: A cross-sectional study using scam vulnerability scale - Ueno, Daisuke; Arakawa, Masashi; Fujii, Yasunori; Amano, Shoka; Kato, Yuka; Matsuoka, Teruyuki; Narumoto, Jin (Frontiers in Psychology, 2022)
Despite the police preventing special fraud victimisation of older adults, both the number of cases and the amount of damage have remained high in Japan. “Special fraud”, in Japan, is a crime in which victims are tricked by fraudsters who through phone or postcards impersonate the victims’ relatives, employees, and other associates, to dupe the victims of their cash or other valuables. The number of recognized cases of special fraud has been turned to increase in 2021. Although police or consumer affairs administrations have been conducting all-encompassing enlightenment or public education for prevention, it is also necessary to reach out to those who are vulnerable to fraud. In this study, we determine the psychosocial characteristics of victims of special fraud in Japanese older adults. We analysed the age, gender, education, residential status, household satisfaction, risk perception, and scam vulnerability scale of 56 older adults aged 60 years or older (mean age: 79.34±7.51 years, 49 women) who had been victims of special fraud and 99 older adults aged 60 years or older (mean age: 77.73±5.69 years, 61 women) who had never been victims of special fraud. The study found that the victimised older adults were more likely to be females who live alone and go out less frequently than the non-victimised older adults. The total scores of the scam vulnerability scale were higher among the elderly victims of special fraud compared to those who had never been scammed, suggesting that the psychosocial characteristics of victims of special fraud among older adults are being female, living alone, going out infrequently, having high confidence against fraud victimization, and responding quickly to phone calls and unknown visitors. Therefore, government agencies or family members should take care of older women who meet these characteristics to reduce their contact with fraudsters.